Readiness and acceptance of UNIMAS' undergraduates towards massive open online courses (MOOCS) for learning - Tasnim, Mohd Taib (Universiti Malaysia Sarawak (UNIMAS), 2015)
With increasing needs of learning and development of new technology to fit in that need, a change is needed in the learning curriculum to meet all expectations. Massive Open Online Courses (MOOCs) is any open course offered for unlimited number of participations from any location around the world anytime of the year. The current introduction of MOOCs in Malaysia Higher Education brings the current learning technology upfront to the undergraduates of Malaysian Higher Institution. This research study is conducted to find out University Malaysia Sarawak (UNIMAS') undergraduates' perception towards Massive Open Online Courses (MOOCs) from the point of readiness and acceptance using an integrated model Technology Readiness and Acceptance Model (TRAM). Participants are UNIMAS' undergraduates of all seven faculties and one centre taking Malaysia MOOCs starting in September 2014 and ending on January 2015.210 respondents have answered a set of questionnaires to find out their readiness and acceptance towards this new technology. The findings acquires further initiatives to increase undergraduates' innovativeness in trying out new technology as well as giving out a deep complete comprehension towards understanding the technology itself (MOOCs). It is highly recommended that `blended learning' concept is put into focus to improve and elevates Malaysian Higher Education in line with the global trends.